Manual and Automated Procedures for Compiling a Very Large Sample of Centenarian Pedigrees. Issue 4 (2nd October 2018) - Nebbia, Giacomo; Nussbaum, Lisa; Helmkamp, Annie; Andersen, Stacy; Perls, Thomas; Sebastiani, Paola
Abstract : A large portion of the baby boomer population will live beyond the age of 90 years, and entitlement programs and various insurance products have thus become interested in longevity risk. Beyond cohort life table predictions, actuaries have little to go on in determining which individuals or portions of populations are at increased risk of living to 90 or 100 or even older. We and others have noted strong familial risk for living beyond the oldest one percentile of survival, and we developed an algorithm that uses information about relatives' longevity to compute the chance of an individual surviving to extreme old age. An important step of this work is to compile large samples of pedigrees with and without long-lived family members. Here we describe our process of hand curation of centenarian pedigrees and software that we have developed for the automated construction of such pedigrees using internet-based resources that can support the manual process.